2020
DOI: 10.1093/humrep/deaa208
|View full text |Cite
|
Sign up to set email alerts
|

IVF outcomes in patients with a history of bariatric surgery: a multicenter retrospective cohort study

Abstract: STUDY QUESTION How does a history of dramatic weight loss linked to bariatric surgery impact IVF outcomes? SUMMARY ANSWER Women with a history of bariatric surgery who had undergone IVF had a comparable cumulative live birth rate (CLBR) to non-operated patients of the same BMI after the first IVF cycle. WHAT IS KNOWN ALREADY In the current context of increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 35 publications
3
31
0
7
Order By: Relevance
“…While Goldman et al (2016) reported that miscarriage occurred more often after RYGB (OR 9.81, 95% CI 1.12–85.71), two other articles observed no change in either miscarriage rate (38.7% vs 56.5%, P = 0.256) or recurrent miscarriages (OR 1.8 95% CI 0.6–5.2, P = 0.208) ( Sheiner et al , 2006 ; Grzegorczyk-Martin et al , 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While Goldman et al (2016) reported that miscarriage occurred more often after RYGB (OR 9.81, 95% CI 1.12–85.71), two other articles observed no change in either miscarriage rate (38.7% vs 56.5%, P = 0.256) or recurrent miscarriages (OR 1.8 95% CI 0.6–5.2, P = 0.208) ( Sheiner et al , 2006 ; Grzegorczyk-Martin et al , 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…One article reported no significant difference in AMH between bariatric surgery patients and non-operated obese patients (mean ± SD 4.6 ± 5.4 vs 3.9 ± 4.0 ng/ml, P = 0.08) ( Grzegorczyk-Martin et al , 2020 ). On the other hand, Nilsson-Condori et al (2018) did find a significant decrease in AMH, free androgen index, androstenedione and testosterone 12 months postoperatively ( P < 0.05), whereas SHBG and oestradiol increased significantly ( P < 0.05) and LH and FSH did not change ( P > 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our intervention protocol also aimed to increase moderate physical activity ( van Elten et al , 2018 ), while no intervention on physical activity was included in the RCT reported by Einarsson. Additionally, a recent exploratory retrospective study illustrated that the number of good-quality embryos did not significantly differ between women who underwent bariatric surgery resulting in a mean BMI of 28.9 kg/m 2 and women with a mean BMI of 37.7 kg/m 2 who did not have surgery ( Grzegorczyk-Martin et al , 2020 ). Although the differences between these studies complicate comparisons of the results, all studies point in the same direction: after intervention with diet in combination with exercise, or LCD, or bariatric surgery to reduce body weight in women with obesity, no improvement was found regarding embryo quality or EUR as proxy for embryo quality.…”
Section: Discussionmentioning
confidence: 99%
“…However, given that aging is a complex process, it is difficult to define the threshold point to make it clear that all events have the same result. In addition, ART patients are usually older and more likely to have some reproductive endocrine and pelvic diseases as well as immune system abnormalities 10 , 11 . Patients receiving ART-assisted pregnancy also require large doses of ovarian stimulation drugs, which further increase the possibility of fetal growth restriction and abortion 6 .…”
Section: Introductionmentioning
confidence: 99%